2009
DOI: 10.1093/hmg/ddp208
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of separate, but collaborative functions of the rRNA methyltransferase-related human mitochondrial transcription factors B1 and B2 in mitochondrial biogenesis reveals new insight into maternally inherited deafness

Abstract: Mitochondrial biogenesis is controlled by signaling networks that relay information to and from the organelles. However, key mitochondrial factors that mediate such pathways and how they contribute to human disease are not understood fully. Here we demonstrate that the rRNA methyltransferase-related human mitochondrial transcription factors B1 and B2 are key downstream effectors of mitochondrial biogenesis that perform unique, yet cooperative functions. The primary function of h-mtTFB2 is mtDNA transcription a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
98
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 50 publications
2
98
1
Order By: Relevance
“…12,13 While both human proteins have demonstrable transcription factor activity in vitro and rRNA methyltransferase activity in a bacterial assay system, 14 subsequent studies appeared to arrive at the consensus that h-mtTFB1 primarily, if not exclusively, functions in vivo as the mitochondrial 12S rRNA methyltransferase, while h-mtTFB2 functions as the mitochondrial transcription factor of this type. 15,16 Interestingly, despite this division of labor, these factors cooperate to promote normal mitochondrial biogenesis and, when this coordination is disrupted, cells are more prone to apoptosis in culture. Previous mechanistic studies using purified recombinant mitochondrial transcription components led to the conclusion that the core human transcription machinery is an obligate threecomponent system comprising POLRMT, have been shown to change their composition as a way to adjust mtDNA expression in response to metabolic signals.…”
Section: Human Mitochondrial Transcription Initiation: Lessons From Pmentioning
confidence: 99%
“…12,13 While both human proteins have demonstrable transcription factor activity in vitro and rRNA methyltransferase activity in a bacterial assay system, 14 subsequent studies appeared to arrive at the consensus that h-mtTFB1 primarily, if not exclusively, functions in vivo as the mitochondrial 12S rRNA methyltransferase, while h-mtTFB2 functions as the mitochondrial transcription factor of this type. 15,16 Interestingly, despite this division of labor, these factors cooperate to promote normal mitochondrial biogenesis and, when this coordination is disrupted, cells are more prone to apoptosis in culture. Previous mechanistic studies using purified recombinant mitochondrial transcription components led to the conclusion that the core human transcription machinery is an obligate threecomponent system comprising POLRMT, have been shown to change their composition as a way to adjust mtDNA expression in response to metabolic signals.…”
Section: Human Mitochondrial Transcription Initiation: Lessons From Pmentioning
confidence: 99%
“…Shadel and colleagues reported that TFB1M and TFB2M play crucial but distinct roles in the control of mitochondrial biogenesis in both human and Drosophila cells (7)(8)(9). TFB2M mainly regulates mtDNA replication and mitochondrial gene transcription.…”
mentioning
confidence: 99%
“…The role of h-mtTFA as a transcriptional activator is well documented, but it also has proposed roles in packaging (21)(22)(23) and repair (24) of mtDNA. A paralog of h-mtTFB2, h-mtTFB1 (or TFB1M), that was originally characterized as a mitochondrial transcription factor in vitro (11,25), is the functional ortholog of the bacterial KsgA rRNA methyltransferase that dimethylates a conserved stem-loop in the mitochondrial 12S rRNA (26) and, hence, has a conserved function in mitochondrial ribosome biogenesis (27) and translation (8,12,28) in vivo. That h-mtTFB1 and h-mtTFB2 are derived from an rRNA methyltransferase, suggests a long evolutionary linkage between mitochondrial proteins involved in transcription, translation, and ribosome biogenesis.…”
mentioning
confidence: 99%